Income sources and inequality among ethic minorities in the Northwest region, Vietnam - Tran, Quang Tuyen (ĐHKT, 2016)
This study analyzes the sources of income inequality among ethnic minorities in the Northwest region - the poorest and highest inequality region of Vietnam. Using an analysis of Gini decomposition by income source, the results show that while agricultural income, notably crop income, considerably decreases income inequality, off-farm income sources are found to increase inequality…